TEACHER AS A KEY FIGURE IN MODERNIZATION OF EDUCATION - Ambartsum R. Galustov (Высшее образование в России)
The article discusses the challenges facing the pedagogical education, examines the experience in the organization of the educational process in Armavir State Pedagogical Academy, characterizes the ways of enhancing international cooperation, proposed methods of social support. Special attention is paid to informatization of education, the development of distant learning based on open-source platform Moodle.